2010
DOI: 10.2967/jnumed.110.074971
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cardiac Sympathetic Innervation and Myocardial Perfusion Are Related to Lethal Arrhythmia: Quantification of Cardiac Tracers in Patients with ICDs

Abstract: Despite widespread prophylactic use of implantable cardioverter defibrillator (ICD) therapy, sudden cardiac death and refractory arrhythmia events are still important clinical issues to be overcome. We examined whether the impairment of cardiac sympathetic innervation and myocardial perfusion is responsible for lethal arrhythmic events and has prognostic value by comparing conventional clinical indices. Methods: In consecutive ICDs implanted in 60 patients, cardiac uptake of 123 Imetaiodobenzylguanidine and 99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 40 publications
(53 reference statements)
2
68
0
1
Order By: Relevance
“…Thereafter, several small but important studies (22,(52)(53)(54)(55)(56)(57)(58) showed that excess activation of cardiac sympathetic nerve function and impaired cardiac sympathetic innervation, as assessed with cardiac 123 I-MIBG imaging, are associated with arrhythmogenicity-leading to lethal ventricular arrhythmias, ICD shock against lethal arrhythmia events, and SCD independent of clinical, electrophysiologic, and LVEF symptoms (59). In addition to the assessment of BNP, LVEF, and myocardial viability, cardiac 123 I-MIBG activity is used for the assessment of prognosis and the selection of therapeutic strategy at our institutes (56,57). The incremental prognostic value of this imaging technique is also supported by larger studies (60,61) and by a PET study with 11 Cmetahydroxyephedrine (62).…”
Section: Device Treatment and Cardiac 123 I-mibg Imagingmentioning
confidence: 99%
“…Thereafter, several small but important studies (22,(52)(53)(54)(55)(56)(57)(58) showed that excess activation of cardiac sympathetic nerve function and impaired cardiac sympathetic innervation, as assessed with cardiac 123 I-MIBG imaging, are associated with arrhythmogenicity-leading to lethal ventricular arrhythmias, ICD shock against lethal arrhythmia events, and SCD independent of clinical, electrophysiologic, and LVEF symptoms (59). In addition to the assessment of BNP, LVEF, and myocardial viability, cardiac 123 I-MIBG activity is used for the assessment of prognosis and the selection of therapeutic strategy at our institutes (56,57). The incremental prognostic value of this imaging technique is also supported by larger studies (60,61) and by a PET study with 11 Cmetahydroxyephedrine (62).…”
Section: Device Treatment and Cardiac 123 I-mibg Imagingmentioning
confidence: 99%
“…Increased norepinephrine spillover, decreased norepinephrine content at nerve endings, and sympathetic denervation in failing hearts can be revealed as an increase in 123 I-MIBG washout rate from the heart or a decrease in 123 I-MIBG activity. Several studies have demonstrated that abnormal 123 I-MIBG kinetics are associated with lethal cardiac events in patients with moderate to severe heart failure (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Nishisato et al reported that a combination of H/M and the summed perfusion defect score on 99m Tc-tetrosfomin images separated patients with ICD shocks from those without, with image variables independent and superior to age, sex, SAECG, BNP, medications, inducible arrhythmias, and LVEF in predicting shocks or cardiac death. 122 Kasama et al 123 showed a correlation of abnormally high 123 I-mIBG washout with increased SCD. Tamaki et al compared ECG parameters-HRV, QT dispersion, and SAECGwith 123 I-mIBG findings in 106 patients with LVEF \ 40%, and those with SCD had a lower H/M and higher WR, with ECG variables showing no independent relationship to outcome.…”
Section: Cardiac Arrhythmiasmentioning
confidence: 99%